Issues of maltreatment in high performance athlete development: Mental toughness as a threat to athlete welfare - Kerr, G.; Stirling, A. (The handbook of talent identification and development in sport, 2017)
Mental toughness is widely recognized as a constellation of characteristics that are critical for the development of talent in athletes. In spite of this view, the construct of mental toughness has been criticized as being nebulous and linked with the masculine cultural values of sport. The proposition of this chapter is that mental toughness can also be problematic as coaching practices used to develop mental toughness may threaten the welfare of athletes. More specifically, we propose that efforts to develop mental toughness in athletes can hide or excuse harmful coaching practices such as emotionally abusive coaching behaviours.